A highly selective fluorescent chemosensor for Ag+ based on calix[4]arene with lower-rim proximal triazolylpyrenes - Wang, Nae-Jen; Sun, Chung-Ming; Chung, Wen-Sheng (My University, 2012)
Ligand 3, a calix[4]arene with lower-rim proximal triazolylpyrenes, is a ratiometric fluorescent chemosensor for Ag+ with higher sensitivity compared to ligand 5, a calix[4]arene with lower-rim distal triazolylpyrenes, and the conventional fluoroionophore with non-conjugated triazole and pyrene. In a polar protic solvent, the binding ratios for 3 center dot Ag+ was determined to be 1:1 and the association constant was found to be 7.0 x 10(3) M-1. The detection of Ag+ by ligand 3 even works in aqueous methanol solution. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Chemosensor; Fluorescence; Calix[4]arene; Triazolylpyrene; Click; Excimer